RELASI AGAMA DAN POLITIK DI ACEH PASCA KONFLIK; Pemerintah Indonesia-Gerakan Aceh Merdeka (Jurnal Adabiya, 2021)
This article tries to explain how the relationship between Islam and politics after the conflict between the Government of Indonesia and the Free Aceh Movement (GAM). After the peace agreement between the two parties with the signing of the Helsinki MoU, the Indonesian government interpreted the agreement in Law No. 11 of 2006 concerning the Government of Aceh (UUPA). The presence of the act makes the ulama a partner of the government in running the wheels of government by giving fatwa on issues of government, development, community development, and the economy. Furthermore, after peace, the role of the ulama was not only to give knowledge to the community, some ulama participated in practical politics. This was one of the effects of the UUPA, where Aceh was given the privilege of establishing local political parties. At present some ulama have occupied various positions in party management, and even participated in the regional head election (PILKADA), where religious values are used as a means of gaining power.